Dewey decimal classification and relative index (v.4) - Melvil Dewey; Joan S Mitchell (ed.); Julianne Beall (ed.); Rebecca Green(ed.); Giles Martin (ed.); Michael Panzer (ed.) (Dublin, Ohio : OCLC Online Computer Library Center, Inc., 2011)
Relative Index
Keywords: Classification, Dewey Decimal